The Paramount Importance of Experience and Situations in Dewey's Democracy and Education. Issue 1 (April 2016) - Hildebrand, David L.
Abstract: In this essay, David Hildebrand connects Democracy and Education to Dewey's wider corpus. Hildebrand argues that Democracy and Education 's central objective is to offer a practical and philosophical answer to the question, What is needed to live a meaningful life, and how can education contribute? He argues, further, that this work is still plausible as "summing up" Dewey's overall philosophy due to its focus upon "experience" and "situation, " crucial concepts connecting Dewey's philosophical ideas to one another, to education, and to democracy. He opens the essay with a brief synoptic analysis of Democracy and Education 's major philosophical ideas, moves on to sections devoted to experience and situation, and then offers a brief conclusion. Some mention is made throughout about the surprisingly significant role art and aesthetics can play in education.